A comprehensive study of chalcogenide quantum dot sensitized solar cells with a new solar cell exceeding 1 V output. (December 2015) - Surana, Karan; Mehra, R.M.; Bhattacharya, B.; Rhee, Hee-Woo; Polu, Anji Reddy; Singh, Pramod K.
Abstract: In the last two decades quantum dots (QDs) have attracted research interest all across the globe owing to their unique size-dependent optical and electronic properties. Generally, smaller the size of the crystal, the larger is the energy gap and greater is the difference in energy between the highest valence band and the lowest conduction band. Therefore more energy is needed to excite the dot, and concurrently more energy is released when the crystal returns to its resting state. Chalcogenide QDs have gained worldwide acceptance for their application in quantum dot sensitized solar cells (QDSSC). This review article focuses chiefly on the progress made in chalcogenide QD based solar cells (SC) over the years along with a new type of QDSSC giving an output voltage of over 1 V.